Spontaneous closure of midline diastema following frenectomy - Koora Kiran; Muthu M; Rathna Prabhu (Wolters Kluwer Medknow Publications, 2007)
Maxillary midline diastema is a common aesthetic problem in mixed and early permanent dentitions. The space can occur either as a transient malocclusion or created by developmental, pathological or iatrogenical factors. Many innovative therapies varying from restorative procedures such as composite build-up to surgery (frenectomies) and orthodontics are available. Although literature says every frenectomy procedure should be preceded by orthodontic treatment, we opted for frenectomy technique without any orthodontic intervention. Presented herewith is a case report of a 9-year-old girl with a high frenal attachment that had caused spacing of the maxillary central incisors. A spontaneous closure of the midline diastema was noted within 2 months following frenectomy. The patient was followed up for 4 months after which the space remained closed and there was no necessity for an orthodontic treatment at a later stage.